1998
DOI: 10.1029/97jb03294
|View full text |Cite
|
Sign up to set email alerts
|

Genesis and evolution of unrest episodes at Campi Flegrei caldera: The role of thermal fluid‐dynamical processes in the geothermal system

Abstract: Abstract. We develop a model for describing water flow in a porous medium under the effect of thermal and pressure gradients. The model simulates geothermal systems in calderas. Given the boundary conditions and the fluid-dynamical properties of the medium, the model allows computation, in fluid-dynamical stationary states, of parameters characterizing the flow, such as flow velocity and temperature and pressure distributions at depth. The model is applied to investigate the effects of the local geothermal sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
74
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(76 citation statements)
references
References 15 publications
2
74
0
Order By: Relevance
“…Thus even in the stationary regime, long after the collapse, the nonhydrostatic stress/pressures may be largely sufficient to drive fluid flow from the caldera to the outer side of the fault and overprint or disturb other circulation mechanisms (see Gaeta et al [1998] for such fluid-dynamic effects in ash flow calderas).…”
Section: Numerical Experimentsmentioning
confidence: 99%
“…Thus even in the stationary regime, long after the collapse, the nonhydrostatic stress/pressures may be largely sufficient to drive fluid flow from the caldera to the outer side of the fault and overprint or disturb other circulation mechanisms (see Gaeta et al [1998] for such fluid-dynamic effects in ash flow calderas).…”
Section: Numerical Experimentsmentioning
confidence: 99%
“…Later on, the effects of structural discontinuities in controlling both the magnitude and the spatial extent of ground deformation were introduced (De Natale and Pingue, 1993;De Natale et al, 1997). The role of heating and expansion of hydrothermal fluids during a bradyseismic event was accounted for in a physical model by Bonafede (1991), and later on by other authors who recognized the importance of hydrothermal circulation not only to explain some of the observed ground uplift, but also to account for the following subsidence phase (Gaeta et al, 1998;Orsi et al, 1999;De Natale et al, 2001;Castagnolo et al, 2001). These works provided important insights on recent crises, but are commonly based on simple descriptions of the fluid dynamics, usually accounting for a steady flow of a single-phase fluid (liquid water), of constant properties.…”
Section: Introductionmentioning
confidence: 99%
“…The possible occurrence of a magma reservoir at about 4 km of depth is indicated by the identification of a P-SV converted phase in a seismic profile [Ferrucci et al, 1992], by the maximum depth of earthquakes [Aster et al, 1992 One-dimensional (l-D) and 2-D numerical models based on the application of nonequilibrium thermodynamics to the interaction between a thermal source and the circulation of groundwater in a permeable system [Gaeta et al, 1998] have shown that hydrothermal systems have the effect of amplifying the ground deformation. In fact, they transfer at shallower depth and on larger surfaces the increase of pressure occurring at the base of the layer.…”
mentioning
confidence: 99%